2019
DOI: 10.1016/j.drugpo.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing prohibitionist ideology: A sociocognitive approach to understand opinions on UK drug policy and the law

Abstract: BackgroundThere is increasing support to include people who use drugs (PWUD) into debates about drug policy reform in order to improve policy legitimacy and outcomes. The aim of this paper is thus to critically analyse the perspectives of PWUD on UK drug policy and the law. This is the first empirical study to apply the four philosophical positions that underpin drug policy debates: Millian liberalism, legal moralism, strict libertarianism and paternalism (MacCoun and Reuter, 2001) to understand opinions and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…PWUD have been increasingly included within the practices of drug-use regulation, by being enabled to distribute health and harm reduction information (Lafferty et al 2017). However, there is as yet little sense that they are seen as policy participants (Askew and Bone 2019;also Stevens 2019) which, itself, continues to constitute a stigmatization of PWUD to whom drug policy is applied, rather than being co-produced as is now common in other fields of social policy.…”
Section: Discussionmentioning
confidence: 99%
“…PWUD have been increasingly included within the practices of drug-use regulation, by being enabled to distribute health and harm reduction information (Lafferty et al 2017). However, there is as yet little sense that they are seen as policy participants (Askew and Bone 2019;also Stevens 2019) which, itself, continues to constitute a stigmatization of PWUD to whom drug policy is applied, rather than being co-produced as is now common in other fields of social policy.…”
Section: Discussionmentioning
confidence: 99%
“…It is part reflexive commentary and part methodological 'instruction manual', and its ultimate goal is to contribute something meaningful to the scholarly community of drugs researchers about the ways in which thinking about themselves and their drug use (past or present) can enhance their professional practice. At the time of writing, progressive policy work is underway around including the voices of people who use drugs in drug policy debates, as well as conversations beginning to emerge around the drug use of drugs researcher (see Askew and Bone (2019), Ross (2020), Harris (2015), and then Ross et al (2020) and Wakeman (2014) respectively). Thus, the present article seeks to offer something of a bridge between these two developments by engaging critically and analytically with the use of autoethnography -the ethnographic exploration of the self -in drugs research.…”
Section: Oscar Wilde the Soul Of Man Under Socialismmentioning
confidence: 99%
“…Ritter et al (2018) highlight the importance of creating space and opportunity for the co-production of knowledge, by focusing on the process of participation, and scrambling the divisions between experts and laypersons, in order for new knowledge to emerge to identify drug policy problems and solutions. To avoid tokenistic consultation, Askew and Bone (2019) similarly reflect on the participatory process itself through adopting a sociocognitive approach (SCA) when analyzing their participant interviews on drug policy reform. Spending more time in the field with CSCs could likewise facilitate deeper insights into the clubs’ values and ideologies and the extent to which CSCs and their members internalize and/or challenge prohibition ideology.…”
Section: Our Experiences In Studying Cannabis Social Clubsmentioning
confidence: 99%
“…Spending more time in the field with CSCs could likewise facilitate deeper insights into the clubs’ values and ideologies and the extent to which CSCs and their members internalize and/or challenge prohibition ideology. Indeed, asking CSCs to choose their preferred policy approach could be reductive/prescriptive since Askew and Bone (2019) found that the perspectives of people who use drugs on drug policy and the law can be diverse, complex, and that clarity surrounding regulatory options is needed. Since drug policy making invariably involves questions of values as well as evidence (MacCoun and Reuter, 2001), a meaningful participatory approach would require more time spent in the field (as was the case in S6, for instance).…”
Section: Our Experiences In Studying Cannabis Social Clubsmentioning
confidence: 99%
See 1 more Smart Citation